Priming Dental Pulp Stem Cells from Human Exfoliated Deciduous Teeth with Fibroblast Growth Factor-2 Enhances Mineralization Within Tissue-Engineered Constructs Implanted in Craniofacial Bone Defects. (23rd April 2019) - Novais, Anita; Lesieur, Julie; Sadoine, Jérémy; Slimani, Lotfi; Baroukh, Brigitte; Saubaméa, Bruno; Schmitt, Alain; Vital, Sibylle; Poliard, Anne; Hélary, Christophe; Rochefort, Gaël Y.; Chaussain, Catherine; et al.
Abstract: The craniofacial area is prone to trauma or pathologies often resulting in large bone damages. One potential treatment option is the grafting of a tissue-engineered construct seeded with adult mesenchymal stem cells (MSCs). The dental pulp appears as a relevant source of MSCs, as dental pulp stem cells display strong osteogenic properties and are efficient at bone formation and repair. Fibroblast growth factor-2 (FGF-2) and/or hypoxia primings were shown to boost the angiogenesis potential of dental pulp stem cells from human exfoliated deciduous teeth (SHED). Based on these findings, we hypothesized here that these primings would also improve bone formation in the context of craniofacial bone repair. We found that both hypoxic and FGF-2 primings enhanced SHED proliferation and osteogenic differentiation into plastically compressed collagen hydrogels, with a much stronger effect observed with the FGF-2 priming. After implantation in immunodeficient mice, the tissue-engineered constructs seeded with FGF-2 primed SHED mediated faster intramembranous bone formation into critical size calvarial defects than the other groups (no priming and hypoxia priming). The results of this study highlight the interest of FGF-2 priming in tissue engineering for craniofacial bone repair. Stem Cells Translational Medicine   2019;8:844–857 : Abstract : Priming stem cells from human exfoliated deciduous teeth with fibroblast growth factor-2 within plastically compressed collagen hydrogels improves osteoformation in vivo in the context of craniofacial bone repair with a faster intramembranous bone formation into calvarial bone critical size defects when compared with either of the 2 other groups (no priming and hypoxia priming) that produced smaller amounts of new bone.